Performance evaluation of Brazilian social organizations according to the best international practices - Raptopoulos, M. M.; Simaens, A.; Silva, J. (European Academy of Management Conference, EURAM 2019, 2019)
Brazil, social organizations demonstrate the results generated to the various beneficiaries by measuring their performances based on the objectives, goals and indicators agreed with their supervisory bodies. Therefore, the adoption of best performance evaluation practices is important to ensure adherence to legal and regulatory standards and to support decision making in approving their annual accounts in order to maintain their qualifications and legitimize themselves for the receipt of new investments and financing. Thus, the objective of this research is to demonstrate if the forms of performance measurement used by the social organizations linked to the Ministry of Education in Brazil adhere to the best international practices. In this way, this work presents contributions by establishing a theoretical reference for performance measurement and comparing it with the methodologies applied in Brazil, by conducting a qualitative exploratory research based on multiple case studies in which the secondary data obtained were treated in the form of content analysis. The results showed that the performance evaluation practices adopted by the analyzed institutions do not adhere to international benchmarking. Additionally, this research points out ways to evolve the methodology currently adopted and brings up other fragilities related to transparency, control and supervision by the supervising Ministry.